International standards in sphere of ensuring the protection of human rights to personal liberty - Авдєєва, Ольга Анатоліївна; Авдєєва, Катерина Вадимівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article considers the international instruments ensuring the protection of human rights to personal liberty at the regional, trans-national and national levels. Revealed international Convention, declaring the fundamental principles of the protection of human rights to personal liberty as a principle of counteraction to crimes against individual freedom - the use of slave labor, human trafficking, kidnapping.